The Fundamental Right to Peace in the Constitution - Landa Arroyo, Cesar (2025)
The first modern constitutions emerged after the anti-colonial and liberation wars against European monarchies in the late 18th and early 19th centuries, under universal liberal principles of defending the human person rather than the State; insofar as the State was a necessary evil, as Rousseau believed. Thus, for a perpetual peace it was necessary to place the human person —their dignity, autonomy, and freedom— as the universal values enabling States to establish a new national and universal order based on human rights, according to Kant.